Management of Adenoid Cystic Carcinoma of the Breast: A Single-Institution Study - Zhang, Wenxiang; Fang, Yi; Zhang, Zhihui; Wang, Jing (Frontiers in Oncology, 2021)
Abstract Objective: The purpose of our study was to analyze the clinicopathologic features and surgical and oncological outcomes of adenoid cystic carcinoma (ACC) of breast and to provide the basis for clinical therapeutic schedule. Methods: A total of 14 patients with primary breast adenoid cystic carcinoma treated in Cancer Hospital of the Chinese Academy of Medical Sciences from January 2000 to December 2017 were searched. Data on clinical presentation, treatment strategy, and outcome, as well as the pathological features of ACC, were reviewed and analyzed. Results: 14 patients were diagnosed with ACC of the breast, out of 23205 total patients treated with breast cancer (0.06%). All but three patients were postmenopausal with a median age at diagnosis of 60.5 years (range, 39 –73 years). The most common clinical presentation was palpable mass (85.7%) and the imaging characteristics of all patients on color Doppler ultrasound and mammography were non-specific. Six patients (42.9%) were suspected of ACC by fine-needle aspiration cytology (FNAC), and were confirmed by postoperative histology and immunohistochemistry. All the 14 patients were taken up for surgery, no patient had positive lymph nodes status. Median tumor size was 1.75 cm (range,1–3 cm). 8/14 (57.1%) patients were hormone receptor (−) (HR−) and HER-2/neu (−) (HER2−), The remaining patients showed hormone receptor positive (HR+). There was no statistical difference in the clinicopathological characteristics between the HR+ group and the HR- group (P＞0.05). The mean follow-up period was 57 months. Local recurrence occurred in 14.3% of patients, 1.7%% of patients had distant metastasis, all patients with local recurrence or distant metastasis were in the HR- group and all patients were alive at last follow-up. Conclusion: ACC of the breast cannot be simply summarized as triple-negative breast cancer, because it also includes a small number of hormone receptor-positive breast cancers. The diagnosis and differential diagnosis are mainly based on pathomor- phological characteristics and immunophenotype. FNAC may be useful in determining treatment strategy. The Breast-conserving surgery may be an alternative treatment strategy and axillary lymph node dissection or sentinel node biopsy may not be necessary in some case.